THE DECALOGUE IN THE NEW TESTAMENT: TRADITION, ETHOS, AND IDENTITY - Punt, J. (Scriptura, 2011)
The presence of the Torah and Decalogue in the New Testament is understandable, given their shared Jewish context; however, the manifestation and utilisation of the Decalogue in the New Testament is as ubiquitous and explicit as it is complex, multi-vocal and multivalent. In this paper two related, important aspects will be argued: firstly, the ethical notions and patterns that emerge in the New Testament, also around and in relation to the Decalogue, naturally have to be understood within their first-century context (or will not be understood at all). Secondly, rather than ‘ethics’, the ethos formations that can be constructed from the New Testament stand in different ways yet in close relation to emerging processes of identity negotiation discernible in New Testament texts. Considering the intersections between Torah/Decalogue, ethos and identity in the New Testament can contribute to discussions on human rights